Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To solve the system of linear equations:
1. [tex]\(3x - y = 11\)[/tex]
2. [tex]\(6x - 3y = 18\)[/tex]
we can approach it step-by-step as follows:
1. First equation:
[tex]\[ 3x - y = 11 \quad \text{(Equation 1)} \][/tex]
2. Second equation:
[tex]\[ 6x - 3y = 18 \quad \text{(Equation 2)} \][/tex]
3. We can simplify Equation 2 by dividing every term by 3:
[tex]\[ \frac{6x}{3} - \frac{3y}{3} = \frac{18}{3} \][/tex]
Simplifying, we get:
[tex]\[ 2x - y = 6 \quad \text{(Simplified Equation 2)} \][/tex]
4. Now, we have a new system of equations:
- [tex]\(3x - y = 11\)[/tex]
- [tex]\(2x - y = 6\)[/tex]
5. To eliminate [tex]\(y\)[/tex], we subtract the second equation from the first:
[tex]\[ (3x - y) - (2x - y) = 11 - 6 \][/tex]
Simplifying this, we get:
[tex]\[ x = 5 \][/tex]
6. With [tex]\(x = 5\)[/tex], we substitute this value back into one of our simplified equations to find [tex]\(y\)[/tex]. Let's use [tex]\(2x - y = 6\)[/tex]:
[tex]\[ 2(5) - y = 6 \][/tex]
Simplifying:
[tex]\[ 10 - y = 6 \][/tex]
Solving for [tex]\(y\)[/tex]:
[tex]\[ y = 10 - 6 \][/tex]
[tex]\[ y = 4 \][/tex]
Thus, the solution to the system of equations is:
[tex]\[ \boxed{x = 5, y = 4} \][/tex]
1. [tex]\(3x - y = 11\)[/tex]
2. [tex]\(6x - 3y = 18\)[/tex]
we can approach it step-by-step as follows:
1. First equation:
[tex]\[ 3x - y = 11 \quad \text{(Equation 1)} \][/tex]
2. Second equation:
[tex]\[ 6x - 3y = 18 \quad \text{(Equation 2)} \][/tex]
3. We can simplify Equation 2 by dividing every term by 3:
[tex]\[ \frac{6x}{3} - \frac{3y}{3} = \frac{18}{3} \][/tex]
Simplifying, we get:
[tex]\[ 2x - y = 6 \quad \text{(Simplified Equation 2)} \][/tex]
4. Now, we have a new system of equations:
- [tex]\(3x - y = 11\)[/tex]
- [tex]\(2x - y = 6\)[/tex]
5. To eliminate [tex]\(y\)[/tex], we subtract the second equation from the first:
[tex]\[ (3x - y) - (2x - y) = 11 - 6 \][/tex]
Simplifying this, we get:
[tex]\[ x = 5 \][/tex]
6. With [tex]\(x = 5\)[/tex], we substitute this value back into one of our simplified equations to find [tex]\(y\)[/tex]. Let's use [tex]\(2x - y = 6\)[/tex]:
[tex]\[ 2(5) - y = 6 \][/tex]
Simplifying:
[tex]\[ 10 - y = 6 \][/tex]
Solving for [tex]\(y\)[/tex]:
[tex]\[ y = 10 - 6 \][/tex]
[tex]\[ y = 4 \][/tex]
Thus, the solution to the system of equations is:
[tex]\[ \boxed{x = 5, y = 4} \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.